Continuous Interscalene Block for Postoperative Analgesia and Shoulder Immobilization After Pectoralis Major Tendon Reinsertion: A Case Report. Issue 6 (15th September 2017) - Finneran, John J.; Ilfeld, Brian M.; Sztain, Jacklynn F.
Abstract : We present the case of a 38-year-old man undergoing surgical repair of his pectoralis major tendon. An interscalene catheter was placed between the middle and lower trunks of the brachial plexus. Postoperatively, ropivacaine 0.2% was infused through postoperative day 3. The patient had excellent pain control requiring minimal opioid analgesics. A catheter between the middle and lower trunks of the brachial plexus provided excellent postoperative analgesia after pectoralis major tendon reinsertion. Additionally, the block likely protected the surgical repair during emergence from anesthesia and in the early postoperative period by providing a motor block of the pectoralis major muscle.